School administrators' leadership practice: a case study related to a new curriculum implementation in Malaysia - Md Ali, Nurul Jawahir; Abdul Kadir, Suhaida; Alwi, Nor Hayati (Human Resource Management Academic Research Society, 2017)
This article used a qualitative case study approach to explore the school administrators’ leadership practice in curriculum implementation of Tahfiz Model Ulul Albab (TMUA) in Malaysia. The paper also aims to identify problem arise due to its implementation as well as administrators’ strategy in tackling the issue. The case study was conducted in a National Secondary Religious School executing the curriculum involving 3 participants, namely the Principal, Senior Assistant 1 and TMUA’s Coordinator. Besides, semi-structured interview, data were collected also by observation and document analysis. The findings indicate several school administrators’ leadership elements under the scope of curriculum implementation, which are ‘goal setting’, ‘instructional management’, ‘leadership control and influence’, ‘motivation’, ‘teacher’s development’, ‘tolerance, communication and interpersonal relationships’, ‘sharing responsibilities and leadership’, ‘foster understanding’, ‘promote religious values’, ‘school ambience’, ‘networking’, ‘financial management’ and ‘innovation’. Challenges in leading the curriculum implementation comprises of three categories, namely ‘system and technical’, ‘teachers’ disciplinary problem’, ‘students’ performance’, ‘parents related issue’ and ‘financial constraint’. This research illustrates the discovery of new leadership dimensions and indicates that the school administrators are practicing more than a single leadership style. This paper also suggests that a proper planning by the policy maker as well as effective administration is necessary in order to ensure the success of the curriculum implementation.